Microscopic colitis in Egyptian population: study of some contributing factors and role of chromogranin A as a diagnostic marker - Mohamed S Gomaa (The Egyptian Journal of Internal Medicine, 2017)
Background Microscopic colitis (MC) and irritable bowel syndrome (IBS) have similar symptoms and a normal endoscopic appearance, as well as normal radiologic findings. Several studies have shown that MC can be mistakenly diagnosed as IBS. Over recent decades, MC has emerged as a common cause of diarrhea, especially in middle-aged or older women, and the disease is regarded as a subgroup within inflammatory bowel disease. The prevalence of MC in Egyptian patients with chronic watery nonbloody diarrhea is high when compared with that in developed countries. MC mainly affects young and middle-aged patients, and it is more commonly of the lymphocytic type. Chromogranin A is a common marker for endocrine cells, and the present finding suggests that colonic hormones are involved in the pathophysiology of lymphocytic colitis (LC). The chromogranin cell density seems to be a good diagnostic marker with high sensitivity and specificity in both the right and left colon; thus, sigmoidoscopy can be used in the diagnosis of LC using this marker. Aim The aim of the current work is to study the prevalence of MC among patient presented with symptoms of IBS. In addition, it is to determine whether chromogranin A cell density is increased in patients with MC and to examine the possibility of using it as a marker for the diagnosis of LC and collagenous colitis. Patients and methods The study was conducted initially on 100 patients presented with symptoms of IBS according to Rome IV criteria. Overall, 50 patients were excluded after finding an organic cause for their symptoms by diagnostic studies. Results A total of 37 cases were diagnosed as having nonspecific colitis, five cases were diagnosed as having MC (10% of the total cases studied), four cases were found to have ulcerative colitis, three cases was found to have eosinophilic colitis, and one case was found to have melanosis coli. Conclusion The initial results of our study revealed that MC is not an uncommon disease, and there was a significant correlation between using NSAID and proton pump inhibitor and smoking, with cases proved to have MC.